Planilha eletrônica para dimensionamento de reforço estrutural de vigas de concreto armado com compósito de fibra de carbono - Verderamo, Bruno Valente [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
One of the main raw materials in the Civil construction sector in Brazil is reinforced concrete, and since the advent of this material in constructions, several techniques have been developed, making the construction and maintenance process of reinforced concrete buildings more advanced. Despite this, the emergence of pathologies in the constructions is becoming more and more frequent and, therefore, the necessity of interventions as well. Among the possible interventions to be carried out are the recovery, repair and structural reinforcement of the construction. In view of this issue, there are many techniques and materials in the market that enable the recovery or reinforcement of construction performance, from the most traditional to the most innovative. Among the innovators, the use of polymeric materials in the structure is emphasized, mainly, the application of the carbon fiber composite that presents itself as an effective technique with several advantages of use. However, the dimensioning of structural reinforcement with carbon fiber composites, especially for flexural reinforced concrete beams, is a complex, time-consuming and inaccurate process. Taking this into consideration, this study is based on the development of an electronic spreadsheet with a user-friendly interface, through researches in articles and books specialized in the application of this material and in the normative considerations about the dimensioning of reinforced concrete beams, that makes the process faster, safer and more accurate sizing. Through the presentation of case studies and the discussion of results comparing the results achieved by manual sizing and through the spreadsheet, it becomes evident the effectiveness and accuracy of the worksheet, as well as if it achieves the desired objectives. In such a way that, with the help of ... (Complete abstract click electronic access below)

Uma das principais matérias-primas do setor da Construção Civil no Brasil é o concreto armado e, desde o advento desse material nas construções, diversas técnicas foram desenvolvidas tornando o processo de construção e manutenção de edifícios de concreto armado mais avançado. Apesar disso, o surgimento de patologias nas construções vem se tornando cada vez mais frequente e, com isso, a necessidade de intervenções também. Dentre as intervenções possíveis de serem realizadas, destacam-se a recuperação, o reparo e o reforço estrutural da construção. Tendo em vista essa questão, existem muitas técnicas e materiais no mercado que possibilitam a recuperação ou reforço do desempenho da construção, desde de as mais tradicionais até as mais inovadoras. Entre as inovadoras, ressalta-se a utilização de materiais poliméricos na estrutura, principalmente, a aplicação do compósito de fibra de carbono que se apresenta como uma técnica eficaz com diversas vantagens de uso. Entretanto, o dimensionamento de reforço estrutural com compósitos de fibra de carbono, especialmente para vigas de concreto armado à flexão, se mostra um processo complexo, demorado e impreciso. Levando isso em consideração, esse estudo se baseia no desenvolvimento de uma planilha eletrônica com interface amigável ao usuário, através de pesquisas em artigos e livros especializados na aplicação desse material e nas considerações normativas acerca do dimensionamento de vigas de concreto armado, que torne o processo de dimensionamento do reforço mais rápido, seguro e preciso. Por meio da apresentação de estudos de casos e pela discussão de resultados que compara os resultados alcançados pelo dimensionamento manual e através da planilha, torna-se evidente a eficácia e precisão da planilha, bem como se atinge ...(Resumo completo, clicar acesso eletronico abaixo)
Spreadsheet for structural reinforcement sizing of reinforced concrete beams with carbon fiber composite
Keywords: Concreto armado; Otimização estrutural; Fibras de carbono; Planilhas eletrônicas; Reinforced concrete